Role of peroxisomes in steroid synthesis in Leydig cells and their influence on male fertility - Kamalyan, Lilit; Justus Liebig University Giessen (My University, 2018)
Infertility is a global health issue, affecting approximately 10-15% of couples worldwide. Male patients with peroxisomal diseases exhibit depending on the phenotype severity either cryptorchidism or a range of testicular pathologies leading in final consequence also to male infertility. Peroxisomes are ubiquitous organelles, which besides other metabolic pathways are involved in ROS-metabolism, cholesterol synthesis and in beta-oxidation of a variety of bioactive lipid derivatives. In this dissertation, the possible role of peroxisomes in Leydig cell steroid metabolism was investigated.The mouse tumor Leydig cell line MLTC-1 and mouse primary Leydig cells were used to knockdown the Pex13 gene by transfection using a Pex13 shRNA plasmid and microporation or Pex13 siRNA and lipofection. The resulting phenotype was characterized by immunofluorescence, Western blots, RT-PCR, Radioimmunoassays, ELISAs and different assays, analyzing ROS metabolism and mitochondrial dysfunction in cells.Our results show that the mouse Leydig tumor cell line MLTC-1 is a good model system to analyze the peroxisomal compartment and steroid synthesis. These cells exhibited, by using the correct cell culture conditions, a strong hCG-mediated increase of steroid synthesis, a typical feature for Leydig cells. We established Pex13 knockdown model in MLTC-1 cells and in primary Leydig cells (Pex13 KD) to study the consequences of peroxisomal dysfunction on steroid synthesis. Western blot and RT-PCR analyses revealed a strong reduction of the Pex13 gene as well as the PEX13 protein in more than 70% of these cells. Moreover, Pex13 KD led to mistargeting of catalase into the cytoplasm in Leydig cells, which is a common phenomenon observed in condition of peroxisomal deficiency. Furthermore, the hCG-mediated induction of the intramitochondrial 30 kDa form of StAR protein (steroidogenic acute regulatory protein) was decreased in Leydig cells with peroxisome deficiency. We also showed that a peroxisomal knockdown leads to significantly reduced levels of progesterone, testosterone and dehydroepiandrosterone (DHEA) synthesis in these cells after stimulation with hCG as well as with 22(R)-Hydroxycholesterol (22R-HC). In contrast, 22R-HC-mediated pregnenolone production was not changed in Leydig cells with peroxisome deficiency. This data indicates that besides StAR, the Pex13 knockdown inhibits 3-hydroxysteroid dehydrogenase (3ß-HSD), and possibly also other steroidogenic enzymes activity downstream of the mitochondrial enzymes such as cytochrome P450c17 (P450c17) and 17ß-hydroxysteroid dehydrogenase (17ß-HSD), whereas, cytochrome P450 side-chain cleavage enzyme (P450scc) activity was not affected, thus, leading to a strong reduction in steroid synthesis. The molecular mechanism explaining the inhibition of androgen synthesis through decreased activity of the above mentioned enzymes in Leydig cell with peroxisome deficiency needs to be further explored. The results of this thesis indicate that peroxisomal deficiency induces mitochondrial disturbance and oxidative stress in Leydig cells. These two organelles exhibit an important functional interplay involving ROS balance, oxidative metabolism of fatty acids and probably other not yet identified functional interactions, one of which might be steroid synthesis. Additionally, knockdown of Mfp2/17-Hsd4 resulted in the inhibition of DHEA production, indicating that peroxisomes could play an important role in the metabolism of steroids.In conclusion, our observations support the conclusion that Pex13 knockdown in MLTC-1 cells and in primary Leydig cells inhibits steroid synthesis due to functional disturbance of peroxisomes and secondary dysfunction of mitochondria.

Die hCG-vermittelte Induktion der intramitochondrialen 30 kDa Form des StAR-Proteins (steroidogenic acute regulatory protein) war in Leydig-Zellen mit Peroxisomenmangel herunterreguliert. Es wurde weiterhin nachgewiesen, dass der peroxisomale Knockdown in diesen Zellen nach Stimulation mit hCG sowie mit 22(R)-Hydroxycholesterin (22R-HC) zu signifikant reduzierten Progesteron-, Testosteron- und Dehydroepiandrosteron (DHEA)-Synthesen führt. Im Gegensatz dazu war die 22R-HC-vermittelte Pregnenolon-Produktion in Leydig-Zellen mit Peroxisom-Mangel unverändert. Diese Daten zeigen, dass neben StAR durch den Pex13-Knockdown auch 3ß-Hydroxysteroid-Dehydrogenase (3ß-HSD) und vermutlich auch andere steroidogene Enzymaktivitäten abwärts der mitochondrialen Enzyme wie z.B. Cytochrom P450c17 (P450c17) und 17ß-Hydroxysteroid-Dehydrogenasen (17ß-HSDs) beeinträchtigt wurden, so dass eine starke Reduktion in Steroidsynthese daraus resultierte. Der molekulare Mechanismus, der zu der Hemmung der Androgensynthese durch eine verminderte Aktivität der oben erwähnten Enzyme in Leydig-Zellen mit peroxisomaler Biogenesestörung führt, muss in weiterführenden Studien noch geklärt werden. Die Ergebnisse dieser Dissertation zeigen auch, dass peroxisomale Biogenesestörungen sekundäre mitochondriale Dysfunktion und oxidativen Stress in Leydig-Zellen induzierten. Diese Biogenesestörungen beiden Zellorganellen zeigen ein wichtiges funktionelles Zusammenspiel in der Regulierung der ROS-Balance, dem oxidativen Metabolismus von Fettsäuren und vermutlich auch anderen, noch nicht identifizierten, funktionellen Interaktionen, von denen eine die Steroidsynthese sein könnte.Darüber hinaus führte der Knockdown von Mfp2/ 17ß-Hsd4 zu einer Hemmung der DHEA-Produktion, was darauf hinweist, dass Peroxisomen eine wichtige Rolle im Metabolismus von Steroiden spielen. Die in der Dissertation gemachten Beobachtungen unterstützen die Schlussfolgerung, dass der Pex13-Knockdown in MLTC-1-Zellen und in primären Leydig-Zellen die Steroidsynthese aufgrund einer funktionellen Störung von Peroxisomen und daraus resultierender sekundären Dysfunktion von Mitochondrien hemmt.
Keywords: ddc:610